Mouse glucocorticoid-induced tumor necrosis factor receptor ligand is costimulatory for T cells - Tone, Masahide (National Academy of Sciences, 2003)
Recently, agonist antibodies to glucocorticoid-induced tumor necrosis factor receptor (GITR) (tumor necrosis factor receptor superfamily 18) have been shown to neutralize the suppressive activity of CD4(+)CD25(+) regulatory T cells. It was anticipated that this would be the role of the physiological ligand. We have identified and expressed the gene for mouse GITR ligand and have confirmed that its interaction with GITR reverses suppression by CD4(+)CD25(+) T cells. It also, however, provides a costimulatory signal for the antigen-driven proliferation of naïve T cells and polarized T helper 1 and T helper 2 clones. RT-PCR and mAb staining revealed mouse GITR ligand expression in dendritic cells, macrophages, and B cells. Expression was controlled by the transcription factor NF-1 and potentially by alternative splicing of mRNA destabilization sequences.